2020
DOI: 10.1097/phh.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Implementation of Play Streets: A Systematic Review of the Grey Literature

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Finally, while the current study focused on the benefits of implementing multiple Play Streets over a limited time period (i.e., one summer). These findings and evaluations out of Chicago and other urban areas suggest value in scheduling Play Streets that recur across multiple years and also recur multiple times within a year [ 11 , 12 , 13 ]. Important considerations for implementers include logistical challenges (e.g., location, date/time, activities, bathrooms), the human resources needed, identification of active play equipment and partners, marketing, and retaining free access to all families, and the potential of competing demands and/or loss of novelty across time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, while the current study focused on the benefits of implementing multiple Play Streets over a limited time period (i.e., one summer). These findings and evaluations out of Chicago and other urban areas suggest value in scheduling Play Streets that recur across multiple years and also recur multiple times within a year [ 11 , 12 , 13 ]. Important considerations for implementers include logistical challenges (e.g., location, date/time, activities, bathrooms), the human resources needed, identification of active play equipment and partners, marketing, and retaining free access to all families, and the potential of competing demands and/or loss of novelty across time.…”
Section: Discussionmentioning
confidence: 99%
“…Play Streets is a place-based intervention in which community members temporarily (2–4 h) close a street or activate a public space, such as a field or a parking lot, to provide a safe place for children to play. While Play Streets have been used in urban areas for decades [ 11 , 12 , 13 ], rural communities have recently adapted them to fit the needs of their communities [ 14 , 15 ]. Play Streets typically occur episodically during the summer (June–September) to provide safe active play opportunities in a time of reduced PA and structured opportunities for activity [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even Brooks et al (2018) verify the importance and utility of grey literature in implementing the managed alcohol programs in hospital settings. Furthermore, Bridges et al (2019) while examining the grey literature reveal its utility in implementing the play streets to create a safe place for active play. Grey literature as an important source in systematic reviews and meta-analysis has been confirmed by Paez (2017).…”
Section: Advantages Of Grey Literaturementioning
confidence: 99%
“…In the United States, play streets have mainly been implemented in urban and suburban communities (Bridges et al, 2020); they have never been implemented in rural communities. This potential expansion of play streets to rural areas is important because individuals living in rural communities face unique obstacles to engaging in regular PA, including dispersed land use, lack of sidewalks, and limited infrastructure such as playgrounds (Umstattd Meyer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%